Data Embedding and Extraction in Scrambled Video using Machine Learning - Ahmed, Afaf Eltayeb Mohamedelbagir (2020)
A Master of Science thesis in Computer Engineering by Afaf Eltayeb Mohamedelbagir Ahmed entitled, “Data Embedding and Extraction in Scrambled Video using Machine Learning”, submitted in December 2020. Thesis advisor is Dr. Tamer Shanableh. Soft copy is available (Thesis, Completion Certificate, Approval Signatures, and AUS Archives Consent Form).